EFFICIENCY OF APPLICATION OF PHASE CONTROL OF ELECTROTRANSMISSION OF HIGH NATURAL POWER CAPACITY - Postolaty V.M. (Problems of the Regional Energetics)
Modeling of power systems, containing a transmission line of high natural power. There are calculated modes of transmission lines and flowing through them power flows at the phase control. There are studied at specific examples of energy systems dependencies of values of fluxes of power along lines of 220,400,500 kV from the angular shift of vectors of voltages which are imposed by phase rotation devices.